Temperature-driven evolution of hierarchical nanodomain structure in tetragonal-like BiFeO3 films - Wang, Lihua (2013)
Transmission electron microscopy study of tetragonal-like BiFeO3 films reveals a hitherto unreported hierarchical nanodomain structure. The 30-50 nm wide stripe domains with {110} domain walls consist of a substructure of lamellar nanodomains of 8-10 nm width in a herringbone-like arrangement. In situ heating and cooling reveal a reversible transition from the hierarchical nanodomain structure to a tweed-like domain structure which is accompanied by a first-order phase transition near 120 °C with a thermal hysteresis.